Can we plan for urban cultural ecosystem sechavices?. Issue 1 (9th August 2020) - Tandarić, Neven; Ives, Christopher D; Watkins, Charles
Abstract: Despite being intangible, subjective and difficult to measure, cultural ecosystem services (CES) are more comprehensible and meaningful to people than many other services. They contribute greatly to the quality of urban life and achieving sustainability. Yet, little attention has been paid to how CES might practically be incorporated into urban planning. This paper addresses this gap by examining the challenges planners might face when handling CES, establishing strategies for addressing the challenges and highlighting key factors planners should consider when planning for CES. CES differ greatly from other ecosystem services—they are definitionally vague, difficult to measure, often bundled with other services and depend on users' perceptions and situational factors. Therefore, rather than adopting a deterministic approach to generating CES, we suggest that urban planners should seek to create opportunities for CES to 'hatch' and 'grow' as people encounter nature in cities. This paper draws from diverse theoretical considerations of the CES concept as well as greenspace planning scholarship and practice. We identify five factors that need to be considered when planning for CES: place, people, past, practices and purpose. We see the proposed '5P' framework as a useful heuristic for planners when implementing CES in urban planning.